Mythology and human nature [soundrecording] - Peck, Morgan Scott 1936- (New York Simon & Schuster, 1991)
Revisits such familiar tales as the story of the Garden of Eden, the myth of the Greek God, Icarus and the legendary conquests of armored knights and the dragons they battled - each time revealing the truths about human nature that these myths and legends address.
Keywords: Myth in literature; Greek mythology; Myth in the bible; Tales; Humanities